The Analysis and Design of a High Efficiency Piezoelectric Harvesting Floor with Impacting Force Mechanism - Sheng-He Wang; Mi-Ching Tsai; Tsung-His Wu (Crystals, 2021)
In renewable energy technology development, piezoelectric material has electro-mechanical converted capability and the advantages of simple construction and compact size, it has potential development since the environment vibration can be transferred into an electrical energy in daily harvesting applications. To improve the electro-mechanical converted efficiency of a piezoelectric harvester at low-frequency environment, a free vibration type of piezoelectric cantilever harvesting structure was proposed, which can generate a resonant oscillation by releasing an initial deformed displacement, and was uninfluenced from the effects of external environment. To analyze the harvesting behaviors, an equivalent circuit with voltage source was provided, and the parameters in theoretical model can be determined by the dimensions of the piezoelectric unimorph plate and its initial deformation. From the comparison of measurement and simulation, it reveals a significant efficient theoretical model where 8% error occurrence for storage energy was found. Finally, the proposed free-vibration generation method was developed in a piezoelectric harvesting floor design, which can transfer human walking motion into electric energy, and store in an external storage capacitor. From the testing result, one time of footstep motion can cause the charging energy in a 33 μF of storage capacitor achieve to 0.278 mJ, which was larger than the driven power of the wireless transmitter module, and then the wireless transmitter can be driven to send a RF signal without external power supply. Therefore, the designed piezoelectric harvesting floor has potential development to locate the user’s current position, which can provide users with future appropriate service for intelligent building application.